Re-conceptualizing joint consultative committees Ii Public higher education sectors in Malaysia - Badariah Ab Rahman; Dzurizah Ibrahim; Rosazman Hussin (2015)
Employee Participation (EP) enhances the quality of decision-making by broadening inputs, promotes commitment to the outcomes, improved motivation, co-operation and communication in the workplace. EP also may reduce workloads of supervisors, encourage skill development in the workforce and can contribute to improved employee relations. There are two forms of EP; direct and indirect. Joint Consultative Committee (JCC) is the most preferred indirect mechanism of workers representation in the UK and other English spoken country such as Australia, New Zealand and the US (Heller, et al. 1998; Parasuraman and Jones, 2006). In the developed countries, the Work Council, a similar structure as JCC can be found in Western Europe (the Netherlands) is the most effective workers representation in EU following the EU Directive 2002 for Information and Consultation (ICE) (Markey, 2010; Goodijk, 2010; Arrigo and Casale, 2010). The ICE has been extended to the UK which has boosted the interest on JCC (Kougiannou, 2013). However, the JCC system and practices in public higher education sector in Malaysia remained to be unknown. This paper discusses on the system and practices of JCC in a public higher education sector in Malaysia. The authors focused on three aspects: what, why and how JCC formation in the public higher education sector, their limitation, evaluation and improvement. The research findings indicate that JCC in public higher education sector was ineffective and re-conceptualizing of the JCC Model is required urgently in order for JCC to be relevant and effective. Therefore, certain modification to the JCC Model is essential to suit the public higher education sector environment in Malaysia.